Access to an anti, syn‐1, 5, 7‐Triol by Configuration‐Encoded 1, 5‐Polyol Synthesis: The C15–C25 Fragment of Tetrafibricin. Issue 14 (13th April 2017) - Friedrich, Ryan M.; Friestad, Gregory K.
Abstract : A configuration‐encoded strategy provides unambiguous stereocontrol in an efficient synthesis of 1, 5‐polyols. To access the anti, syn ‐1, 5, 7‐triol moiety of the C15–C25 fragment of tetrafibricin, a fibrinogen receptor antagonist, a strategy is introduced, which sequences the 1, 5‐polyol synthesis with selective desilylation and diastereoselective intramolecular conjugate addition. For tetrafibricin, assembly of the C15–C25 anti ‐1, 5‐diol in five steps is followed by the conjugate addition to introduce a syn ‐1, 3‐diol to complete the anti, syn ‐1, 5, 7‐triol unit and to provide the functionality and stereochemistry required for tetrafibricin synthesis. Abstract : A strategy that sequences configuration‐encoded 1, 5‐polyol synthesis with diastereoselective intramolecular conjugate addition accesses the C15–C25 anti, syn ‐1, 5, 7‐triol of tetrafibricin, a fibrinogen receptor antagonist. Assembly of the anti ‐1, 5‐diol is followed by conjugate addition to introduce a syn ‐1, 3‐diol to provide the functionality and stereochemistry required for tetrafibricin synthesis.